Health Supplement Consumption Behavior in the Older Adult Population: An Exploratory Study - TSE, Mimi M.Y.; CHAN, Ka Long; WONG, Anthony S.W.; TAM, Eric W.C.; FAN, Elaine Y.L.; YIP, Gloria P.C. (Frontiers in Public Health, 2014)
Health supplement consumption behavior is important to maintain health status. The purpose of the study was to explore the spending pattern on health supplement consumption behavior in Hong Kong older adults population. The present study was a cross-sectional survey study; and was collected from via a street-intercept interview. Participants were approached and invited to response to a questionnaire. The location for data collection was evenly distributed in Hong Kong, Kowloon and New Territories. The questionnaire included demographic data and source of income source, spending habits on health supplement products and whether they performed regular health check. There were 982 participants interviewed; and 46% was male and 54% was female. The participants are divided into young-old (age 50-69) and old-old group (age 70 or above). The mean age is 67.93±10.386. Most of the participants have regular body check; the major reason is to maintain health. Less than half of the participants spent money on health supplement products; the major reason for such purchase was to maintain health; while for not buying is they did not think that would have any effect in their health. Also, more young-old participants have regular body check and spend more money on health supplement products; while old-old group participants were less likely to concern their health, and they were less likely to perform regular body check and purchase health supplement products. The present research reveals the pattern of the health supplement consumption behavior of young-old and old-old. Young-old group and old-old group have difference pattern according to their difference age-related health condition and the amount of spare money. Different educational programme concern health consciousness and promotion strategy of regular body check and health supplement products need be tailor-made for older adults, and for young old and old-old groups.